2006
DOI: 10.1016/s0001-2092(06)60116-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hypothermia—The chilling consequences

Abstract: UNPLANNED HYPOTHERMIA is commonly encountered in the perioperative period. Nursing has contributed to the literature on hypothermia with studies on shivering and treatment modalities; however, the direct physiological consequences of postoperative hypothermia have been reported mainly in the medical literature. RESEARCH ON THE PHYSIOLOGICAL effects of postoperative hypothermia offers nurses further evidence to support interventions for temperature correction in patients with hypothermia. Evidence indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 20 publications
0
40
0
2
Order By: Relevance
“…The physiological effects reflect an overall depression of metabolism affecting all body systems (Table 2). 4,5,8,[10][11][12][13] In addition to the physiological effects of hypothermia, other potentially deleterious effects include alteration in wound healing, myocardial infarction, coagulopathy, increased infection rates, and prolonged emergence after anesthesia because of decreased drug metabolism, as well as psychological effects including pain, stress, and altered cognitive functioning (Table 3). 12 Although all patients are potentially affected by the adverse physiological responses associated with hypothermia, infants, the elderly and debilitated, patients with burns and trauma, and the malnourished represent patient categories at greatest risk for developing physiological alterations (Table 4).…”
Section: Physiological Alterations Secondary To Hypothermiamentioning
confidence: 99%
See 4 more Smart Citations
“…The physiological effects reflect an overall depression of metabolism affecting all body systems (Table 2). 4,5,8,[10][11][12][13] In addition to the physiological effects of hypothermia, other potentially deleterious effects include alteration in wound healing, myocardial infarction, coagulopathy, increased infection rates, and prolonged emergence after anesthesia because of decreased drug metabolism, as well as psychological effects including pain, stress, and altered cognitive functioning (Table 3). 12 Although all patients are potentially affected by the adverse physiological responses associated with hypothermia, infants, the elderly and debilitated, patients with burns and trauma, and the malnourished represent patient categories at greatest risk for developing physiological alterations (Table 4).…”
Section: Physiological Alterations Secondary To Hypothermiamentioning
confidence: 99%
“…12 Although all patients are potentially affected by the adverse physiological responses associated with hypothermia, infants, the elderly and debilitated, patients with burns and trauma, and the malnourished represent patient categories at greatest risk for developing physiological alterations (Table 4). 5,8 For example, research aimed at predictive factors for hypothermia found that patients older than 70 years were at greater risk for untoward sequelae associated with the development of perioperative hypothermia. 14…”
Section: Physiological Alterations Secondary To Hypothermiamentioning
confidence: 99%
See 3 more Smart Citations